Edupreneurship untuk Mewujudkan Madrasah Mandiri Berprestasi melalui Pendirian Badan Usaha - Fadlil, Anis Sulkhan (QuranicEdu: Journal of Islamic Education, 2024)
Madrasah independence must always be pursued both in relation to attitudes (soft skills) and funding. As an alternative solution, edupreneurship which is interpreted as entrepreneurship education or entrepreneurship in the education sector needs to be presented to bridge this problem. MI Ma'arif Garongan implements the edupreneurship concept by creating a Madrasah-Owned Enterprise (BUMM) in the form of a minimarket called MIMAGA MART. The existence of MIMAGA MART has had a significant impact both on madrasah finances in general, improving salaries for honorary teachers and educational services. The aim of preparing this paper is to examine the steps towards madrasah independence and its impact on madrasahs. The preparation method used is qualitative research with a focus on literature study and field study. The sample used was madrasa heads by collecting data through interviews and field studies. The data that has been collected is then processed using content analysis. This paper concludes that of the many edupreneurship implementations, the establishment of Madrasah-Owned Enterprises (BUMM) is quite effective and realistic to implement in realizing madrasa independence.